2022
DOI: 10.37992/2022.1304.158
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic effectiveness, efficiency and dose optimization of gamma rays in papaya (Carica papaya L.) varieties

Abstract: The present study was conducted to determine the mutagenic effectiveness, efficiency and lethal dose of gamma rays in papaya varieties CO7, Arka Prabhath and Arka Surya. Papaya seeds were exposed to various doses of gamma rays (0Gy, 100Gy, 150Gy, 200Gy, 250Gy, 300Gy, 350Gy, 400Gy, 450Gy and 500Gy) and the mutagenic effectiveness and efficiency of gamma rays were assessed based on the chlorophyll mutation frequency and biological damage in M 1 plant basis. There was a negative relationship between mutagenic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…In general, it was observed that the germination, survival, and growth rate of papaya exhibited a downward trend as the gamma irradiation dosages were raised. According to Ravi et al (2022), Signi cantly, the ndings of this study are consistent with previous research conducted by Zamir et al (2003), which also reported that the percentage of sprouting was greater at lower concentrations of irradiation doses compared to higher concentrations in Guava plants. This observation indicates that the trend observed in the sprouting buds could perhaps be attributed to the carcinogenic impact of irradiation on chromosome abnormalities.…”
Section: Discussionsupporting
confidence: 92%
“…In general, it was observed that the germination, survival, and growth rate of papaya exhibited a downward trend as the gamma irradiation dosages were raised. According to Ravi et al (2022), Signi cantly, the ndings of this study are consistent with previous research conducted by Zamir et al (2003), which also reported that the percentage of sprouting was greater at lower concentrations of irradiation doses compared to higher concentrations in Guava plants. This observation indicates that the trend observed in the sprouting buds could perhaps be attributed to the carcinogenic impact of irradiation on chromosome abnormalities.…”
Section: Discussionsupporting
confidence: 92%